Determinan Pemanfaatan Buku Kesehatan Ibu dan Anak (Kia) Oleh Ibu Hamil Di Puskesmas Wanakerta Kabupaten Karawang Tahun 2015 - Nita Farida (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2016)
MCH handbook is expected to increase community participation in controlling maternal health. Results of the coverage achievement of this handbook until December 2014 from Kerawang Health Office amounted to 63.49% and the coverage of V1 was 93.37% and this indicates a difference in which in fact both coverages should be the same as the MCH handbook is given when mothers check their pregnancy for the first time. This study aimed to obtain the utilization of MCH Handbook by pregnant women and factors associated with the utilization of MCH handbook in pregnant women in Wanakerta health center, Karawang regency in 2015. The study design was cross-sectiona The population in this study were all pregnant women at Wanakerta health center who did checkups and the sample was part of pregnant women who already had the MCH handbook, and came to checkups at Wanakerta health center in June 2015. The results of this study showed that the variables associated with the use of MCH handbook in this study were education, attitudes, support for health personnel, health cadre support, and family support. Meanwhile, age, parity, and socioeconomy were not related to the utilization of MCH handbook by pregnant women.